2019
DOI: 10.1016/j.jphotobiol.2019.111514
|View full text |Cite
|
Sign up to set email alerts
|

Retinal degeneration rat model: A study on the structural and functional changes in the retina following injection of sodium iodate

Abstract: Retinal disorders account for a large proportion of ocular disorders that can lead to visual impairment or blindness, and yet our limited knowledge in the pathogenesis and choice of appropriate animal models for new treatment modalities may contribute to ineffective therapies. Although genetic in vivo models are favored, the variable expressivity and penetrance of these heterogeneous disorders can cause difficulties in assessing potential treatments against retinal degeneration. Hence, an attractive alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…Therefore, going forward to in vivo studies, we focused solely on miR-144-3p. We evaluated the impact of miR-144-3p suppression in the sodium iodate mouse model, an established model of pro-oxidant induced outer retinal damage [[28], [29], [30], [31],[46], [47], [48], [49]]. In brief, sodium iodate (50 mg/kg i.p) was used to induce retinal degeneration; anti-miR-144-3p or vehicle (control) was injected sub-retinally on the following day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, going forward to in vivo studies, we focused solely on miR-144-3p. We evaluated the impact of miR-144-3p suppression in the sodium iodate mouse model, an established model of pro-oxidant induced outer retinal damage [[28], [29], [30], [31],[46], [47], [48], [49]]. In brief, sodium iodate (50 mg/kg i.p) was used to induce retinal degeneration; anti-miR-144-3p or vehicle (control) was injected sub-retinally on the following day.…”
Section: Resultsmentioning
confidence: 99%
“…Although, this in vitro study reported a correlation between miR-144 and Nrf2, the specific involvement of 5p or 3p variant and the in vivo effects of miR-144 were not studied. In the present study, we evaluated the relevance of miR-144 to the expression of Nrf2 and downstream Nrf2 target genes in cultured human RPE and, to overall retinal health in the sodium-iodate mouse, a classic rodent model of oxidant-induced retinal degeneration [[29], [30], [31], [32]].…”
Section: Introductionmentioning
confidence: 99%
“…Retinal degeneration in post-transplanted (4-day) Sprague-Dawley rats (herein designated as day 0 in the present study) were induced using a systemic administration of sodium iodate (NaIO 3 ) as per our previous study (Koh et al, 2019). The compound was prepared fresh by diluting NaIO 3 (Alfa Aesar, MA, United States) in sterile Hank's balanced salt solution (10% w/v) and stored at RT before administration.…”
Section: Sodium Iodate Degeneration Modelmentioning
confidence: 99%
“…In this study, we aimed to investigate the therapeutic potential of MSCs EPO in a rat retinal degeneration model that was established using NaIO 3 (Koh et al, 2019). Firstly, MSCs EPO were cultured and expanded until the cells were sufficient enough for intravitreal transplantation into the sodium iodate-induced model.…”
Section: Introductionmentioning
confidence: 99%
“…It is experimentally capable of forming retinitis pigmentosa or age-related macular degeneration in animals. Also, in these animal studies, sodium iodate at doses of 20 to 80 mg/ kg was used to create retinal toxicity [7]. In an animal study, Moriguchi et al have showed that retinal toxicity, due to sodium iodate, is reversible at low doses and irreversible at high doses [8].…”
Section: Discussionmentioning
confidence: 99%